Análise dos casos de morbidade, Near Miss e óbito materno em uma Unidade de Terapia Intensiva na região norte do Ceará - Rios, Ana Jéssica Silveira (2022)
Objective: To analyze cases of near miss and maternal death in the Intensive Care Units (ICU) of a hospital in the Superintendence of the Northern Region of the state of Ceará. Method: Analytical, cross-sectional epidemiological study. Data collection was carried out from May to July 2022 at Santa Casa de Misericórdia in Sobral (SCMS), Ceará, Brazil. The study population consisted of all the medical records of women who had been admitted to the two SCMS ICUs between the years 2011 to 2020 (n=173). The following exclusion criteria were applied: medical records with incomplete data; not found; cases of indirect pregnancy complications and accidental or incidental causes, with 47 records excluded, totaling a sample of 149 records. Data were collected from an instrument adapted from the World Health Organization (WHO) to identify maternal near miss (MNM). Afterwards, they were compiled and analyzed using the Stata program. Results:There were 75 cases of MNM; 32MM; the severe maternal outcome was 107; RNMM was 46.9 per 1000 LB; the NMM:MM ratio was 2.3:1; the ICU MMR was 20,000/100,000 LB; and MI was 29.9%. The age between 20-35 years, compared to less than 20 years, showed a higher risk of MNM and MM, as well as having 2 or 3 diagnoses. Pregnancy of less than 37 weeks was associated with MNM. Severe pre-eclampsia and HELLP Syndrome were the main admission diagnoses. CPAV were associated with MNM and death. Clinical, laboratory and management criteria were the most common. All NMM and MM events had dysfunction, the most frequent being cardiac, respiratory and hematological. In perinatal outcomes, APGAR < 7 at the fifth minute was associated with postpartum women who died. Conclusion:Hypertensive syndromes are the main forms of admission in the study setting. Potentially fatal complications and interventions were associated with MNM or MM, reiterating the importance of monitoring morbidities from the perspective of preventing undesirable outcomes. Added to this, the NMM criteria were able to identify all MM, demonstrating that the WHO approach is efficient and, when used, can announce the sequence of dysfunctions that culminate in death.